Instructional design: A framework for designing web-based courses - Ling, Siew Woei (2003)
The educationists have adopted the World Wide Web for being a teaching and learning tool. Being a new mode of instruction, learning is surrounded by many uncertainties as to the best way to develop it. In many cases, the new features of technology and designer's intuition are dictating the design of web-based courses. Many web-based courses do not seem to be grounded on a solid instructional framework. As such, current scaffoldings tend to tail to support effective learning in web-based courses.